Fine-needle aspiration cytology findings in human immunodeficiency virus lymphadenopathy - Vanisri H; Nandini N; Sunila R (Wolters Kluwer Medknow Publications, 2008)
Thirty-six human immunodeficiency virus (HIV)-positive patients with lymphadenopathy were subjected to fine-needle aspiration cytology (FNAC) over a period of 2 years. The maximum number of cases was reported in the age group of 21 to 30 years. Majority of the patients were males. The maximum number of cases had tuberculosis (58.3%) followed by reactive lymphadenitis (36.1%), non-Hodgkin′s lymphoma (2.7%) and acute suppurative lymphadenitis (2.7%). FNAC is an important diagnostic tool in the evaluation of lymphadenopathy in HIV-positive patients.